It's a small world : worldwide declining attendance and Disney theme parks - Gigliotti, Robert; Russell, Adam; Gentry, Richard J. ([London] : SAGE, 2016)
The global recession that began in 2008 affected the global theme park industry, and with it the theme park empire of The Walt Disney Company. This case examines the trends assessment and decision making required of Jay Rasulo, chair of Walt Disney Parks and Resorts, in response to these economic challenges.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Walt Disney Company; Amusement parks -- Case studies; Decision making -- Case studies; Consumer satisfaction -- Case studies; International business enterprises -- Management -- Case studies; Strategic planning -- Case studies